Treatment of Alfalfa Seeds With Food-grade Organic Acid Mixtures Reduces Loads of Pathogenic Escherichia coli O157:H7 and Salmonella Typhimurium on Sprouts Without Reducing Germination Percentage or Sprout Mass - David F. Bridges; Alexander R. Hendricks; Nicholas J. Colella; W. Scott Compel; Maeli Melotto (Journal of Food Protection)
Sprouts are regarded as premier health foods due to their high content of vitamins and minerals. Unfortunately, numerous outbreaks of foodborne illness have been linked to raw sprouts due to their capacity to harbor bacterial pathogens combined with growing conditions favoring microbial growth. One commonly utilized practice to reduce microbial hazards on fresh sprouts is treatment of seeds with 20,000 ppm sodium hypochlorite (NaClO) or calcium hypochlorite (Ca(ClO)2). However, these traditional chlorine-based treatments have a limited capacity to reduce the population growth of pathogens during sprout development and might affect the safety of workers and health of consumers; thus, alternative treatments are needed. Promising alternatives to chlorine-based sanitizers are organic acids. We have investigated the capacity of novel matrices comprised of organic acids (OAM), consisting of unique mixtures of zinc acetate (Zn(CH3CO2)2), citric acid (HOC(CH2CO2H)2), malic acid (HO2CCHCH2CO2H), and lactic acid (C3H6O3) to reduce loads of human pathogenic bacteria Escherichia coli O157:H7 and Salmonella Typhimurium inoculated on alfalfa sprouts (∼6 log CFU/ml). Seed treatment with OAM formulations prior to germination resulted in approximately 100-fold reductions and was superior to treatment with solutions containing only the base organic acid ingredients of the OAMs, but not as significant as the 20,000 ppm NaClO treatments which consistently reduced pathogen loads over 1000-fold. However, all OAM treatments resulted in significantly increased germination percentages (89.0–95.3%) compared to 20,000 ppm NaClO treatments (85%). Fresh sprout weight measured after 5 days for 3 of the 4 tested OAMs (100 sprout batches; 2.31–2.62 g) was also significantly higher than fresh weights after NaClO treatment (∼2.0 g). Our results indicate a promising step towards implementing treatments that decrease sickness risks from consuming fresh sprouts without compromising production yield.